Midostaurin in patients with acute myeloid leukemia and FLT3-TKD mutations: a subanalysis from the RATIFY trial - Voso, Maria Teresa; Schlenk, Richard Friedrich (Blood advances, 2020)
The results from the RATIFY trial (ClinicalTrials.gov: NCT00651261; CALGB 10603) showed that midostaurin combined with standard chemotherapy significantly improved outcomes in patients with FMS-like tyrosine kinase 3 (FLT3)-mutated acute myeloid leukemia (AML), compared with placebo. In this post hoc subgroup analysis from the trial, we evaluated the impact of midostaurin in 163 patients with FLT3-tyrosine kinase domain (TKD) mutations. At a median follow-up of 60.7 months (95% CI, 55.0-70.8), the 5-year event-free survival (EFS) rate was significantly higher in patients treated with midostaurin than in those treated with placebo (45.2% vs 30.1%; P = .044). A trend toward improved disease-free survival was also observed with midostaurin (67.3% vs 53.4%; P = .089), whereas overall survival (OS) was similar in the 2 groups. Patients with AML and NPM1mut/FLT3-TKDmut or core binding factor (CBF)-rearranged/FLT3-TKDmut genotypes had significantly prolonged OS with or without censoring at hematopoietic cell transplantation (HCT), compared with NPM1WT/CBF-negative AMLs. The multivariable model for OS and EFS adjusted for allogeneic HCT in first complete remission as a time-dependent covariable, revealed NPM1 mutations and CBF rearrangements as significant favorable factors. These data show that NPM1 mutations or CBF rearrangements identify favorable prognostic groups in patients with FLT3-TKD AMLs, independent of other factors, also in the context of midostaurin treatment.